Silicato de cálcio no manejo do meloeiro e na qualidade dos frutos pós-colheita - Cruz, Beatriz Leticia Silva da (Universidade Federal Rural do Semi-Árido, 2016)
The melon is a crop of great economic importance to Brazil and especially in the Northeast region, where production is mainly for the foreign market. Phytosanitary problems of culture, however, are numerous and have increased the need to use pesticides, considering that the ones allowed for this culture are increasingly scarce in the country and foreign market. The use of alternatives to improve the plant health and fruit quality is welcome and essential to a more sustainable agriculture and less damaging to the environment. This study aimed to evaluate the effect of calcium silicate in the management of leafminer and powdery mildew melon crop and quality of post-harvest fruits. The experiment was conducted at Agrícola Famosa farm, located in the municipality of Baraúna, Rio Grande do Norte, Brazil. In the first stage of experiment, we evaluated the effect of calcium silicate in the plant of melon and in the second, we evaluated physical and chemical qualities of postharvest melon. For phytosanitary analysis, we were assessed the severity of powdery mildew and the number of leafminer mines in the area that received and not calcium silicate, using a completely randomized design and 26 repetitions. The evaluations were performed at 7, 14, 21, 28 and 35 days after removal of TNT manta. At the end of the cycle, in order to analyze the quality of post-harvest fruit, 75 fruit each area with and without calcium silicate were picked at random and evaluated for physical and chemical characteristics in 5 storage periods (0, 21, 28, 35 and 42 days) and 5 replicates, with 3 fruits per repetition. The experimental design was completely randomized. Calcium silicate reduced the severity of powdery mildew and leaf lesions caused by leafminer and provided firmer, less mass loss and pulp thickness and did not alter the chemical characteristics such as pH, total soluble solids and titratable acidity of fruits post-harvest
Keywords: Cucumis melo; Indutor de resistência; Silício; Cucumis melo; Resistance inducer; Silicon; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA